Social media and its impacts on the youths of Thimphu ([Thimphu] : [Royal Thimphu College], 2017)
Spiral-bound xerographic copy.
Student research project for BA, Political Science (Capstone Project):(2017).
Includes bibliographical references.
Keywords: Communication Social aspects Bhutan; Mass media Social aspects Bhutan; Capstone Project